Characterization of Bacillus subtilis and Paenibacillus polymxa strains to reduce disease incidence of Fusarium Wilt Disease and enhance production of resistant and susceptible Chickpea varieties under greenhouse conditions - Urgessa Ensermu (ASTU, 2022)
Plant Growth Promoting Rhizobacteria (PGPR) are one of the major components of the soil microbial populations, which play significant roles in improving plant growth and protecting plants from disease of which spore forming bacteria such as Bacillus and Paenibacillus are widely known as main contributors to disease management by induction of host defenses and biological control of pathogens. Therefore, the aim of the present study was to characterize and evaluate the potential of selected four Bacillus and one Paenibcillus strains to inhibit Fusarium oxysporum, decrease wilt diseases and improve production of four chickpea genotypes;i.e Dhera, JG-62, Eshete and Habru .The experimental design was a randomized complete block design with three replication. The greenhouse treatment includes five strains of paenibacillus polymxa (ALCR-42), and Bacillus subtilus (ALCR-45, ALCR-46, ARC-262 and ARC-358) strains against Apronstar Fungicides (positive control) and non-bioprimed seeds (negative control).The ecophyisiological characteristics like temperatures, salinity, pH tolerance, carbon, nitrogen source utilization pattern, fungicide resistance, shelf life of the isolates on different carriers were also assessed to select best formulation that favours for long storage period. The ability of the isolates in promoting plant growth parameters was measured using agronomic parameter and the data were analyzed by one way ANOVA. The result showed that the bacillus and Paenibacillus strains exhibited 53–65 % growth inhibition against Fusarium oxysporum, of which ARC-358, ALCR-46, ALCR-262 and ALCR-45 exerted their higher inhibitory effect of 65%, 64.11%, 63.7 % and 61.69% against F. oxysporum ceceri, respectively. In addition, the greenhouse study also indicated that the highest percent wilt disease incidences were observed in JG-62 treated with ALCR-42 (55%) and minimum percent of wilt diseases incidence was observed in JG-62 treated with ARC-262 (22%). The results from growth parameters indicated that Bacillus subtilis strains ARC-262 and ARC-358 induced the highest biomass on all chickpea genotypes. In general, the results suggested the application of bioinoculants of rhizobacteria under a competitive environment can be explored as bio-protectants for improving productivity and suppression of Fusarium wilt in chickpea. However, the application of present findings required further trials under field conditions.
Keywords: Antagonistic; Biological control; Fusarium wilt; Rhizobacteria